Hubungan Paparan Media Sosial dengan Pencegahan Pernikahan dini di Wilayah Pertanian Kabupaten Jember - Nur Akmala Dewi (Fakultas Keperawatan, 2025)
Introduction: Teenagers’ social media exposure to early marriage varied between individuals because not all teenagers optimized social media as an educational tool related to early marriage. Therefore, the prevention of early marriage in Indonesia was still inadequate. This study aimed to analyze the correlation between social media exposure and early prevention in the agricultural area of Jember Regency. Method: This study used a correlational descriptive approach with a cross-sectional research design. The research sample consisted of 318 respondents who were selected using the cluster random sampling technique. Result: The correlation between social media exposure and early marriage prevention was significant (ρ-value <0.001, r= 0.199). The results of this study aligned with the research hypothesis, namely that there was a correlation between social media exposure and early marriage prevention in the agricultural area of Jember Regency. Analysis: The lack of exposure to social media about early marriage was caused by the insufficient use of social media as an educational tool related to the prevention of early marriage. Optimizing the use of social media as an educational tool was identified as one of the efforts to prevent early marriage because higher exposure to social media about early marriage formed an attitude supporting decision-making to avoid early marriages. Discussion: Optimizing social media exposure as a medium for information related to early marriage was needed to increase knowledge about the dangers of early marriage, thereby preventing early marriages from occurring.
Reuplod Repository Ratna 14 Juli 2026 Validasi dan Finalisasi Ratna 14 Juli 2026
Keywords: teenagers; social media exposure; prevention of early marriage